(untitled) (Open Academia: Journal of Scholarly Research, 2024)
Education should be done primarily by parents in the family, neighbors and community activists, and teachers at school should always be aware of this. In educational activities and in a group of peers, a young student, first of all, forms willful character traits such as independence, self-confidence, responsibility, determination, endurance. The formation of moral behavior is a multifaceted activity of children. Self-control is an important feature of the will of a young student. Leontiev showed that boys are the most impulsive in their behavior, and girls are restrained